Advanced mosasaurs from the Upper Cretaceous Nakaminato Group in Japan. (16th November 2021) - Kato, Taichi; Nakajima, Yasuhisa; Shiseki, Kohei; Ando, Hisao
Abstract: Plotosaurus is a highly aquatically adapted mosasaur, which is supposed to inhabit the deep ocean basin. The geographic occurrence of this genus has been limited only to the west coast of North America. In this study, two Plotosaurus ‐type mosasaur caudal vertebrae derived from the Upper Cretaceous Nakaminato Group in Ibaraki Prefecture, Japan, are described with discussion on the paleobiogeographic significance of the Late Cretaceous mosasaur fauna in the Northwestern Pacific region. The two specimens are an intermediate caudal vertebra found in a beach cobble, which presumably originated from the Hiraiso Formation (upper Campanian), and a terminal caudal vertebra found in situ in the lower Isoai Formation (lower Maastrichtian). Because their relative centrum lengths (ratio of centrum length/centrum height, ~0.7) are very close to that of Plotosaurus, the specimens are referred to cf. Plotosaurus sp. The two specimens provide the first evidence that highly specialized Plotosaurus ‐type mosasaurs inhabited the Northwestern Pacific Ocean, suggesting that such forms had a wider distribution than previously recognized and might have existed since the late Campanian in the Northwestern Pacific Ocean.